Membangun Etika Pergaulan Remaja melalui Bimbingan Klasikal di SMP Muhammadiyah 6 Samarinda - Marsela Puji Lestari; Isnaini Septian Nur Rochmah; Annisa Nanda Rahmadani; Siti Anisatus Zahrok; Nur Indah; Ziyada Tsaniya; Rudy Hadi Kusuma (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2025)
Adolescence is an important period in the formation of a person's personality, where individuals tend to be easily influenced by the social environment including associations. Unhealthy associations have the potential to cause various problems such as peer pressure, low self-confidence, and the emergence of deviant behavior. This service activity aims to increase the awareness and understanding of Muhammadiyah 6 Samarinda Junior High School students regarding the importance of applying ethics in society through the provision of classical guidance services. The activity, which carries the theme "Ethics in Society: Fun Friends Are Not Toxic", was held for three days on May 14-16, 2025, with three main sessions lasting 150 minutes every day. The material provided includes the introduction of the concept of social ethics, identification of healthy and unhealthy associations, ethical values in Islam, and ethics of behavior on social media. Through participatory and reflective methods, students are invited to actively discuss, conduct social simulations, and reflect on the values learned. The results of the evaluation showed an increase in student understanding, changes in social attitudes, and openness in communicating with guidance and counseling teachers.